The teddy bear chronicles - Xi, Xi (Hong Kong Literature Series., 2020)
This is a most unusual book. For several decades Xi Xi has been widely known for her award-winning poetry and fiction. This time, she has chosen to write about the teddy bears she began making in 2005, after treatment for cancer, in order to improve the mobility of her right hand. She made the bears herself from scratch, choosing some of her favourite characters from history and legend such as the Taoist philosopher Master Zhuang, the Mongol ruler Genghis Khan, and Beauty and the Beast. She also created exquisite items of clothing for them and wove a series of delightfully witty essays around them, giving her readers fascinating insights into Chinese culture, and into the ways in which Chinese clothing and fashion have evolved through the ages. This is a book for all who love literature and teddy bears.